2004
DOI: 10.1002/app.20249
|View full text |Cite
|
Sign up to set email alerts
|

Pore structure of water‐wettable hydrophobic resins based on divinylbenzene and methyl acrylate

Abstract: ABSTRACT:Hydrophobic, but water-wettable porous resins based on divinylbenzene (DVB) and methyl acrylate (MA) were prepared with a wide range of pore structures by suspension copolymerization under different conditions. By using purified DVB (98.8%), the specific surface area for the resulting MA/DVB resins could reach high values at high DVB levels, while these resins are wettable by direct contact with water. An increased content of MA significantly increases the porosity of the resins, whereas the solvating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…However, those phenomena are not obvious in the precursor resin PDM-40, which can be attributed to the fact that there are almost no pendant vinyl groups onto PDM-40. Similar results were reported by Nyhus et al [41] and Yan and co-authors [42]. Resins EGDMAco-DVB were prepared by the copolymerization of EGDMA and DVB, and some typical properties are presented in Table 1.…”
Section: Resultssupporting
confidence: 68%
“…However, those phenomena are not obvious in the precursor resin PDM-40, which can be attributed to the fact that there are almost no pendant vinyl groups onto PDM-40. Similar results were reported by Nyhus et al [41] and Yan and co-authors [42]. Resins EGDMAco-DVB were prepared by the copolymerization of EGDMA and DVB, and some typical properties are presented in Table 1.…”
Section: Resultssupporting
confidence: 68%
“…The literature suggests that the resin synthesis must be in a three-neck polymerization reactor. 29,51 The synthesis involved 60, 29, 10, and 1 wt% of DVB, MA, AS (or PdAS), and AIBN:…”
Section: Synthesis Of Pdas(10) Ms and Pdas (10) Os Resinsmentioning
confidence: 99%
“…Porous polymer-resins were synthesized via suspension polymerization using a modied procedure reported in detail by Wei et al 14 The co-monomers (MA and x-N(CH 2 CH 2 Cl) 2 where x: Alk or Acy) were rst mixed well with the porogen (toluene) and DVB as crosslinker, in mass ratio 2 : 39 : 60, to form an organic phase in which the initiator, AIBN, was added (1 wt% monomers-based). The organic phase mixture was then added, at a 1 : 3 ratio (v/v), to the aqueous phase containing 0.2% hydroxyethyl cellulose and 20% NaCl, and the polymerization was allowed to proceed at 70 C and 85-90 C for 14 and 4 h, respectively.…”
Section: Synthesis Of Porous Polymer-resinsmentioning
confidence: 99%
“…5 In recent years, suspension polymerization is used to produce crosslinked-polymers with a controllable pore structure and a high surface area compared to Merrield resins. [12][13][14] These materials contain well-developed micropores and mesopores, therefore should decrease the diffusion limitations and signicantly improve the accessibility to the reactive pending groups and produce highly dispersed catalysts. [15][16][17] In this way, Canali et al 18 have reported a porous polystyrene/ polymethacrylate-based resin with supported Jacobsen's chiral Mn-saliciden-ethylenediamine complexes for alkene enantioselective oxidation.…”
Section: Introductionmentioning
confidence: 99%